A feasibility study on integrating the Philippine government documents collection of the University of the Philippines National College of Public Administration and the Governance library to the digital archives at UP Diliman - Dela Cruz, Terrence S. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
The UP NCPAG Library's Philippine Government Documents Collection holds great legal and cultural value due to the nature of its contents. However, the collection is, at the time of speaking, in very bad condition and lacks any preservation policies. This feasibility study explores the possibility of integrating the collection into the Digital Archives @ UP Diliman (DA@UPD) for the purpose of access and preservation.